When Viruses Don't Go Viral: The Importance of Host Phylogeographic Structure in the Spatial Spread of Arenaviruses - Gryseels, Sophie; Baird, Stuart J E; Borremans, Benny; Makundi, Rhodes; Leirs, Herwig; Goüy de Bellocq, Joëlle (PLoS pathogens, 2017)
Many emerging infections are RNA virus spillovers from animal reservoirs. Reservoir identification is necessary for predicting the geographic extent of infection risk, but rarely are taxonomic levels below the animal species considered as reservoir, and only key circumstances in nature and methodology allow intrinsic virus-host associations to be distinguished from simple geographic (co-)isolation. We sampled and genetically characterized in detail a contact zone of two subtaxa of the rodent Mastomys natalensis in Tanzania. We find two distinct arenaviruses, Gairo and Morogoro virus, each spatially confined to a single M. natalensis subtaxon, only co-occurring at the contact zone's centre. Inter-subtaxon hybridization at this centre and a continuum of quality habitat for M. natalensis show that both viruses have the ecological opportunity to spread into the other substaxon's range, but do not, strongly suggesting host-intrinsic barriers. Such barriers could explain why human cases of another M. natalensis-borne arenavirus, Lassa virus, are limited to West Africa.
Keywords: Animals; nemoci hlodavců; Phylogeography; Disease Reservoirs; Rodent Diseases; Tanzania; zdroje nemoci; druhová specificita; lidé; Murinae; Species Specificity; Tanzanie; Lassa Fever; horečka Lassa; fylogeografie; Arenavirus; zvířata; virus Lassa; Lassa virus; Humans